My Summer Internship Programme - Dedhia, Vatsal (ATLAS SkillTech University, 2024)
Objective: To gain practical experience in a real-world work environment, develop strong communication skills, navigate the challenges of social media management, and build a professional network. 1. Develop Effective Communication Skills: Enhance verbal and written communication skills by actively engaging in various communication tasks within the organization. This includes drafting compelling social media content, collaborating with team members, and effectively conveying ideas and information. 2. Navigate Social Media Challenges: Gain hands-on experience in managing social media platforms by strategizing, creating content, and engaging with the audience. Learn how to address and overcome challenges such as handling negative feedback, responding to customer inquiries, and maintaining brand consistency across different platforms. 3. Adapt to a Real-World Work Environment: Acclimate to the demands of a professional work environment, including meeting deadlines, collaborating with diverse teams, and managing priorities effectively. Develop a strong work ethic, attention to detail, and the ability to work autonomously and within a team setting. 4. Networking and Professional Relationship Building: Actively engage with professionals in the organization to build a strong professional network. Seek opportunities to connect with colleagues, attend company events, and participate in meetings to establish relationships that can provide guidance, mentorship, and potential future career opportunities.
Project Report on My Summer Internship Programme (2022-2024) Under the Guidance of Prof. Tapish Panwar
Keywords: Networking; Professional Relationship Building; Real-World Work Environment; Social Media; Communication Skills